A structural relationship model of green cleaning for healthcare facilities in Malaysia / Adriana Kamaruddin - Kamaruddin, Adriana (2022)
The development of green cleaning as a push to accomplish sustainability has prompted the necessity for a new approach to building maintenance and operations, especially in the cleaning aspect. Green cleaning is products or services that have a lesser or reduced effect on human health and the environment when compared with competing products or services that serve the same purpose. Proper cleaning can significantly reduce a patient's chance of infection with healthcare-acquired pathogens. However, conventional cleaning presents diverse health and environmental problems that can only be addressed by green cleaning. Hence, healthcare facilities require green cleaning services to render economic, social, and environmental benefits. However, without clear green cleaning components and requirements, the management does not know what cleaning service providers are supposed to provide in their service to ensure the healthcare facility's cleaning is carried out effectively and efficiently. Therefore, this research aims to explore the relationship between green cleaning components for healthcare facilities in Malaysia. The objectives of this research are: 1) To identify the components and requirements of green cleaning for healthcare facilities in Malaysia; 2) To examine the validity of green cleaning for healthcare facilities, and 3) To establish the structural model of green cleaning for healthcare facilities. The research methodology adopted to achieve the aim of the study was conducted in three phases. In the first phase, eight components of green cleaning were identified from the kinds of literature, achieving the first objective.